Sosialisasi dan Pelatihan Penyusunan Laporan Keuangan Bagi UMKM di Desa Giling, Kecamatan Pabelan, Kabupaten Semarang - Nur Anita; Niswah Baroroh; Muhammad Khafid (Pusat Riset dan Inovasi Nasional, 2025)
This community service activity aims to improve the financial literacy of MSMEs in Giling Village, Pabelan District, Semarang Regency, through training on preparing simple financial reports. The training was conducted over one day and attended by 20 MSMEs from various business sectors, such as culinary, handicrafts, and trade. The methods used in this training included socialization of basic accounting materials tailored to the level of understanding of the participants, as well as hands-on practice in preparing financial reports, such as profit and loss statements and balance sheets. The material was presented in a simple and easy-to-understand manner, so that participants could immediately apply it to their businesses. Evaluation was carried out by observing the process of preparing financial reports by participants, using the provided practice sheets, and a feedback questionnaire that measured the extent of participants' understanding and changes in attitudes. The results of this activity showed that most participants were able to understand basic accounting concepts and were able to prepare simple financial reports quite well. This was also followed by an increase in participants' awareness of the importance of neat and orderly recording of daily transactions in running a business. Furthermore, this training succeeded in motivating participants to apply what they had learned in their respective businesses independently. Although this activity was short-lived, it had a very positive impact in building a strong foundation for more orderly and transparent financial governance among MSMEs. Therefore, it is recommended that follow-up training and regular mentoring be conducted to ensure the skills acquired can be applied sustainably and improve the ability of MSMEs to manage their finances professionally. Furthermore, this activity also provided a deeper understanding of the importance of sound financial planning for those wanting to start a business.